EATING BEHAVIOR AND OBESITY: UNDERSTANDING THE PSYCHOLOGICAL LINK - Magfirat Mirodil kizi Abdumutalibova (Bright Mind Publishing, 2025)
This article explains the aspects of how eating behavior is related to weight gain. It provides information about how psychological processes in a person's lifestyle are connected to their eating habits.
Keywords: Obesity, eating behaviour, eating habits, restrained eating, emotional eating.